2009
DOI: 10.1016/j.ophtha.2009.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Macular Ganglion Cell Loss in Glaucoma by Fourier-Domain Optical Coherence Tomography

Abstract: Purpose-To map ganglion cell complex thickness with high-speed Fourier-domain optical coherence tomography (FD-OCT) and compute novel macular parameters for glaucoma diagnosis.Design-Observational, cross-sectional study.Participants-One hundred seventy-eight participants in the Advanced Imaging for Glaucoma Study, divided into three groups: 65 persons in the normal group (N), 78 in the perimetric glaucoma group (PG), and 52 in the pre-perimetric glaucoma group (PPG). Methods-TheRTVue FD-OCT system was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
573
6
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 607 publications
(622 citation statements)
references
References 44 publications
28
573
6
15
Order By: Relevance
“…13,14 GCC are affected by multiple diseases such as glaucoma and macular degenerations which caused structural changes in the retina and choroid. Tan et al, 13 reported that retinal nerve fiber layer and ganglion cell thickness were significantly lower than normal group in glaucoma patient. This result has showed that ganglion cell layer thickness measurement was important for glaucoma diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 GCC are affected by multiple diseases such as glaucoma and macular degenerations which caused structural changes in the retina and choroid. Tan et al, 13 reported that retinal nerve fiber layer and ganglion cell thickness were significantly lower than normal group in glaucoma patient. This result has showed that ganglion cell layer thickness measurement was important for glaucoma diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ganglion cell complex thickness in AMD E Yenice et al there is no available literature that investigated ganglion cell complex thickness with the SD-OCT in this patient group. 13,15 In a study, which was performed histopathological manner in AMD donors, GCL and photoreceptor topography was measured and GCL neurons survival level and relationship between photoreceptor loss was examined in the same eyes. These study findings were 47% loss of GCL neurons in end-stage cases of exudative AMD (EAMD) but preservation of GCL neurons in NEAMD.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of spectral domain optical coherence tomography (SD-OCT) allows us to measure the ganglion cell complex (GCC, the combination of retinal nerve fiber, retinal ganglion cell and inner plexiform layers) covering the central macula. Previous studies demonstrated that GCC thickness was significantly lower in glaucomatous eyes with visual field defects than in healthy eyes [13,14]. A number of studies report a high correlation between global visual field sensitivity and GCC in glaucomatous subjects using SD-OCT [15,16].…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have shown SDOCT mGCC measurements to have similar ability to detect glaucoma as cpRNFL (Schulze et al, 2011;Tan et al, 2009), with similar findings also observed using mGCIPL measurements (Akashi et al, 2013;Jeoung et al, 2013;Kotowski et al, 2012;Mwanza et al, 2012;Nouri-Mahdavi et al, 2013). Mzanwa and colleagues recently demonstrated average mGCIPL thickness to have excellent ability to differentiate healthy and glaucomatous eyes, with an AUC of 0.935, which was almost identical to the AUC of cpRNFL of 0.936.…”
Section: Imaging the Maculamentioning
confidence: 53%